An investigation into the ride comfort of buses using an air suspension system. (5th June 2021) - Tan, Vu Van; Hung, Truong Manh; Sename, Olivier
The paper focuses on the ride comfort criteria of a two-axle bus using an air suspension system. First of all, based on the Gensys model, a nonlinear model of an air spring element linked to an auxiliary air tank is investigated. The parameters of the air spring model are determined through real experiments in both static and dynamic load modes with the error between the theoretical simulation model and the real experimental data being less than 8%. Then, a full bus model using the dependent suspension system takes into account the driver model mentioned in two cases of using air suspension and leaf suspension. Simulation results in the time domain with different motion states show that the ride comfort of the bus using air suspension system is improved by about 20%, when compared to the bus using the leaf suspension system. Meanwhile, the road holding criteria are maintained.